National Federation of Women Workers Unemployment Benefit Demonstration, 1920 (1920)
1920 1918-1939 "National Federation of Women Workers Unemployment Benefit Demonstration, 1920" [T0114.jpg], 1920 With unemployment rising steeply in 1920, an expanded Unemployment Insurance Act was introduced. A campaign for equalisation of men's and women's benefits under the Act was rejected. Moreover, women were refused benefit if they rejected work in domestic service. The National Federation of Women Workers (NFWW) set up its own unemployment benefit scheme, offering 18 shillings per week instead of 12 shillings under the Government scheme.